2021
DOI: 10.3389/fspor.2021.768846
|View full text |Cite
|
Sign up to set email alerts
|

Gastrocnemius Muscle Architecture in Elite Basketballers and Cyclists: A Cross-Sectional Cohort Study

Abstract: Eccentric and concentric actions produce distinct mechanical stimuli and result in different adaptations in skeletal muscle architecture. Cycling predominantly involves concentric activity of the gastrocnemius muscles, while playing basketball requires both concentric and eccentric actions to support running, jumping, and landing. The aim of this study was to examine differences in the architecture of gastrocnemius medialis (GM) and gastrocnemius lateralis (GL) between elite basketballers and cyclists. A train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 126 publications
(189 reference statements)
0
8
0
Order By: Relevance
“…Measures of skeletal muscle architecture were done using two-dimensional B-mode ultrasound (Mindray Diagnostic Ultrasound System). Here, muscle thickness represents the most employed measure of muscle dimension ( Sarto et al, 2021 ) according to its correlation to muscle cross-sectional area, which is proportional to the number of parallel sarcomeres, thereby influencing maximal force production ( Lieber & Fridén, 2000 ; Narici et al, 2016 ; May et al, 2021 ). In our examination, ultrasound images from the lateral gastrocnemius were recorded using a linear transducer with a standardized frequency of 12–13 MHz.…”
Section: Methodsmentioning
confidence: 99%
“…Measures of skeletal muscle architecture were done using two-dimensional B-mode ultrasound (Mindray Diagnostic Ultrasound System). Here, muscle thickness represents the most employed measure of muscle dimension ( Sarto et al, 2021 ) according to its correlation to muscle cross-sectional area, which is proportional to the number of parallel sarcomeres, thereby influencing maximal force production ( Lieber & Fridén, 2000 ; Narici et al, 2016 ; May et al, 2021 ). In our examination, ultrasound images from the lateral gastrocnemius were recorded using a linear transducer with a standardized frequency of 12–13 MHz.…”
Section: Methodsmentioning
confidence: 99%
“…30% of the distance between the articular cleft of the knee joint to the most lateral top of the lateral malleolus was used to place the transducer (Perkisas et al, 2021). The muscle belly was determined as the center of the muscle between its medial and lateral borders where the maximal MCSA can be assumed (Fukunaga et al, 1992;May et al, 2021). In addition, the image plane is best aligned with the muscle's fascicles including minimal fascicle curvature (Bénard et al, 2009;Raj et al, 2012;May et al, 2021).…”
Section: Sonographymentioning
confidence: 99%
“…The muscle belly was determined as the center of the muscle between its medial and lateral borders where the maximal MCSA can be assumed (Fukunaga et al, 1992;May et al, 2021). In addition, the image plane is best aligned with the muscle's fascicles including minimal fascicle curvature (Bénard et al, 2009;Raj et al, 2012;May et al, 2021). To improve acoustic coupling and to reduce the transducer's pressure on the skin before starting the measurement, a transmission gel was applied.…”
Section: Sonographymentioning
confidence: 99%
See 1 more Smart Citation
“…US can be used in a wide variety of people ranging from extremely lean to obese, [24] and has been applied in various groups, including basketball players. [22,[25][26][27][28][29] However, to the best of our knowledge, no study has simultaneously reported the US normative values for GM and RF (muscle thickness [MT] and SFT), comparing these results between different age-categories and genders in young elite basketball players. Considering all the above, the aims of the present study were to (1) obtain normative data from physical tests [CMJ and V-cut] and ultrasound measurements [MT and the adjacent SFT of the GM and RF] of different age-category male and female elite youth basketball players; (2) evaluate possible between-agecategory (U14, U16, and U18) and between-gender (male or female) differences in all these data; and (3) examine the relationships between physical and US measurements and determine the combination of variables that most accurately predict the abilities of jumping and sprinting with COD in males and females.…”
Section: Accepted Manuscriptmentioning
confidence: 99%